Computationally efficient winding loss calculation with multiple windings, arbitrary waveforms, and two-dimensional or three-dimensional field geometry. - Sullivan, C.R.
The squared-field-derivative method for calculating eddy-current (proximity-effect) losses in round-wire or litz-wire transformer and inductor windings is derived. The method is capable of analyzing losses due to two-dimensional and three-dimensional field effects in multiple windings with arbitrary waveforms in each winding. It uses a simple set of numerical magnetostatic field calculations, which require orders of magnitude less computation time than numerical eddy-current solutions, to derive a frequency-independent matrix describing the transformer or inductor. This is combined with a second, independently calculated matrix, based on derivatives of winding currents, to compute total AC loss. Experiments confirm the accuracy of the method
Keywords: 2-D field geometry; 3-D field geometry; Arbitrary waveforms; Eddy-current losses; Frequency-independent matrix; Inductor windings; Litz-wire transformer windings; Multiple windings; Numerical magnetostatic field calculations; Proximity-effect losses; Round-wire transformer windings; Squared-field-derivative method; Total AC loss; Transformer winding loss calculation